2019
DOI: 10.4103/ijcm.ijcm_346_18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implementation of “Kayakalp” initiative on quality certification of district hospitals to National quality assurance standards

Abstract: Background:Ministry of Health and Family Welfare has developed National Quality Framework to assess the quality of services for improvement and helps in certification of facilities, while Kayakalp was launched to promote cleanliness and hygiene in public health facilities.Objective:The objective of the study is to assess if Kayakalp implementation within the public health facilities supports quality certification of health facilities.Methods:A retrospective study was designed to gather data for 32 quality-cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Eleven studies evaluated the impacts of various forms of regulation of health facilities on QoC 232–242. In South Africa, hospital accreditation was associated with improved compliance with quality standards.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies evaluated the impacts of various forms of regulation of health facilities on QoC 232–242. In South Africa, hospital accreditation was associated with improved compliance with quality standards.…”
Section: Resultsmentioning
confidence: 99%
“…The accreditation of health service providers linked to insurance payments in the Philippines improved quality scores among physicians in both public and private hospitals 238. Studies based on quality certification programmes were found in Egypt,236 India232 and Tanzania 237. In Ethiopia, clinical and administrative standards implementation improved quality in all areas assessed 234.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations